Early optical observations of seven gamma-ray bursts in comparison to their gamma X-ray characteristics in the MSU MASTER Global Robotic Telescopes Net - V. M. Lipunov; N. V. Tyurina; V. G. Kornilov; E. S. Gorbovskoy; V. V. Vladimirov; A. S. Kuznetzov; P. V. Balanutsa; D. S. Zimnukhov; V. V. Chazov; D. M. Vlasenko; A. G. Tlatov; V. A. Senik; et al. (Геодинамика и тектонофизика, 2019)
Seven gamma-ray bursts – GRB 130907A, GRB 140311B, GRB 140129B, GRB 160227A, GRB 120404A, GRB 110801A, and GRB 120811C were observed by the MSU MASTER (Mobile Astronomical System of TElescope Robots) Global Network. Full automation of the observations provided for obtaining unique data on the properties of early optical radiation accompanying gamma-ray bursts. The data are compared in the optical (MASTER), X-ray (SWIFT X-ray Telescope, XRT) and gamma (SWIFT Burst Alert Telescope, BAT) ranges. Based on the data obtained, two groups are identified, and their radiation mechanisms are revealed. The effect of gamma-ray bursts on the biosphere of the Earth is determined, and the estimates and the scale of such an effect are considered.